Numerical investigation of air enclosed wave impacts in a depressurised tank. (1st September 2016) - Ma, Z.H.; Causon, D.M.; Qian, L.; Mingham, C.G.; Martínez Ferrer, P.
Abstract: This paper presents a numerical investigation of a plunging wave impact event in a low-filling depressurised sloshing tank using a compressible multiphase flow model implemented in open-source CFD software. The main focus of this study is on the hydrodynamic loadings that impinge on the vertical wall of the tank. The detailed numerical solutions compare well with experimental results and confirm that an air trapped plunging wave impact causes the vertical wall to experience pulsating pressure loadings in which alternate positive and negative gauge pressures occur in sequence following the first applied pressure peak. The strongest pulsations of the pressure are found to be near the air pocket trapped by the water mass. The instantaneous pressure distribution along the vertical wall is nearly uniform in the area contained by the air pocket. The phases of pulsating pressures on the wall are in synchronisation with the expansion and contraction of the trapped air pocket. The pocket undergoes changes in shape, moves upwards with the water mass and eventually breaks up into small parts. A careful integration of the wall pressure reveals that the vertical structure as a whole experiences pulsating horizontal impact forces. It is found that the average period of pulsation cycles predicted in the present study is around 5–6 ms, and the loading pulsations are quickly damped out in 0.1 – 0.2 s . Further exploratory investigation of the fluid thermodynamics reveals that the temperature inside the trapped air pocket rises quickly for about 2 ms synchronised with the pocket's first contraction, then the generated heat is rapidly transferred away in around 3 ms. Abstract : Highlights: The pressure-based compressible code can properly deal with multiphase free surface flows consisting of nearly incompressible low-speed and compressible regions. The predicted pressure loadings agree well with the experimental results regarding the amplitude and phase. The crucial pulsation of pressures in synchronisation with the contraction and expansion of the trapped air pocket is successfully handled. Exploratory investigation reveals that the trapped air pocket has a short thermal pulsation, which requires innovative ways to accurately measure the temperature with a high sample rate.